Effect of moisture on the processability and physical properties of natural rubber - Perera, M.C.S.; Siriwardena, T.A.S. (Rubber Research Institute. Agalawatte, 1985)
The natural rubber absorbs moisture when exposed to high humuditiess. The presence of moisture is found to reduce the mastication efficiency of rubbers resulting in stocks with high Mooney viscosities. The green strenth and the die swell increases as a result. It has also been found that this affects the milling efficiency resulting in heterodlsperse stocks. These effects could be climinated by further milling. The presence of moisture, however, affects directly, the Mooney scorch time of conventional mixes, the tensile strength, resilience and heat build - up
Keywords: Industries; Rubber; Water uptake; Humidity; Vulcanization